Assessment and Impact of Technology-Based Self-Directed Learning of Anatomy Among Clinical and Anatomy Students in Two Universities - Ikpeze, Somadina Chiagozie; Ama, Ifeanyichukwu Maxwell; Anosike, Ifeanyi Uzochukwu; Nwovu, Friday Christian (British Journal of Healthcare and Medical Research, 2024)
Global lockdown occasioned by COVID-19 pandemic showed that students in Nigeria ought to have continued learning at home if digital technologies were adequately deployed. Impact of technology-based self-directed learning of anatomy on academic performance was evaluated in a 10-month longitudinal cross-sectional study among 268 volunteer preclinical and anatomy students of two universities in South East Nigeria. Validated electronic questionnaire was used to extract information on students’ demographics, knowledge, perceptions and use of technology-based self-directed learning of anatomy, as well as their average performance in most recent anatomy examinations. Anatomy and preclinical students’ ratio was 41.8:58.2 but females and age-group of 21-25 years contributed 63.1 and 52.2% of the participants, respectively. About 69.4% of the students used smart phones, 46.3% downloaded one or no anatomy software while 49.6% experienced 5-9 hours daily phone-screen-time. Significant association was found between knowledge of technology-based self-directed learning and performance in anatomy courses (χ²=8.239; p=0.044). Respective 5.2%, 28.7%, 61.2%, and 4.9% of the students never, rarely, sometimes, and often used technology-based self-directed learning of anatomy. Students with good knowledge of technology-based self-directed learning (Adjusted OR = 1.049, p=0.007) are 1.05 times more likely to progress from lower to higher performance level when use and perception of technology-based self-directed learning are constant. Faculties should develop anatomy software, as well as provide computerized classrooms and laboratories for enhanced technology-based self-directed learning of anatomy.